Synthesis of planar chiral compounds containing α-amino phosphonates for antiplant virus applications against potato virus Y - Deng, Youlin (2024)
An unprecedented study of the application of planar chiral compounds in antiviral pesticide development is reported. A class of multifunctional planar chiral ferrocene derivatives bearing α-amino phosphonate moieties was synthesized. These compounds, exhibiting superior optical purities, were subsequently subjected to antiviral evaluations against the notable plant pathogen potato virus Y (PVY). The influence of the absolute configurations of the planar chiral compounds on their antiviral bioactivities was significant. A number of these enantiomerically enriched planar chiral molecules demonstrated superior anti-PVY activities. Specifically, compound (Sp, R)-9n displayed extraordinary curative activities against PVY, with a 50% maximal effective concentration (EC50) of 216.11 μg/mL, surpassing the efficacy of ningnanmycin (NNM, 272.74 μg/mL). The protective activities of compound (Sp, R)-9n had an EC50 value of 152.78 μg/mL, which was better than that of NNM (413.22 μg/mL). The molecular docking and defense enzyme activity tests were carried out using the planar chiral molecules bearing different absolute configurations to investigate the mechanism of their antiviral activities against PVY. (Sp, R)-9n, (Sp, R)-9o, and NMM all showed stronger affinities to the PVY-CP than the (Rp, S)-9n. Investigations into the mechanisms revealed that the planar chiral configurations of the compounds played pivotal roles in the interactions between the PVY-CP molecules and could augment the activities of the defense enzymes. This study contributes substantial insights into the role of planar chirality in defending plants against viral infections.